The regulation of human eosinophil function by endogenous mono-hydroxy-eicosatetraenoic acids (HETEs) - Goetzl, E J; Weller, P F; Sun, F F (The Journal of immunology (1950), 1980)
The possibility that endogenous mono-hydroxy-eicosatetraenoic acids (HETEs) derived from the lipoxygenation of arachidonic acid might influence the functions of human eosinophils from hypereosinophilic subjects was examined by analyzing both the activities of the purified HETEs and the effects of depletion of intracellular HETEs on eosinophil migration. Incubation of arachidonic acid with the 17,000 × G supernatant from homogenates of human eosinophils generated predominantly 11-HETE, 9-HETE, and 5-HETE. The same mono-HETEs and 5,12-di-HETE were the major products extracted from intact eosinophils. The ratio of the quantity of 9-HETE to that of 8-HETE generated by eosinophil homogenates and recovered from intact eosinophils exceeded 6, as contrasted with 0.75 for human neutrophils, whereas the eosinophil content of 5-HETE was less than that of the human neutrophil. The incubation of eosinophils with the calcium ionophore A23187 or with chemotactic fragments of C5 (C5fr) substantially elevated the cellular content of 5-HETE and produced lesser increases in the levels of 11-HETE and 5,12-di-HETE. Maximal eosinophil chemotactic responses of comparable magnitude were elicited by the HETEs which displayed a distinct rank-order of potency of 5-HETE>9-HETE>11-HETE. Eosinophil chemokinesis and the expression of eosinophil C3b receptors were optimally stimulated by 1 to 2 µg/ml of each of the native HETEs, whereas peak chemokinetic and chemotactic concentrations failed to influence the expression of IgG-Fc receptors or the release of the eosinophil enzymes β-glucuronidase and arylsulfatase B. Preincubation of eosinophils with the lipoxygenase inhibitors 5,8,11,14-eicosatetraynoic acid (TYA) at a concentration of 10 µM or nordihydroguaiaretic acid (NDGA) at a concentration of 5 µM depleted the unstimulated eosinophil content of HETEs by 41 to 60% and the C5fr-stimulated eosinophil content of HETEs by 65 to 83%, and concomitantly inhibited random migration and chemotaxis to a significant extent. The addition of purified native HETEs to the HETE-depleted eosinophils restored migration to normal levels. The most potent principle in reversing inhibition was the 5-HETE. Thus, the HETEs generated by eosinophils potentially may fulfill a role as endogenous cellular mediators as well as exhibiting the capacity to evoke inflammatory responses.